Pengembangan Media Pembelajaran Smart Reading Board untuk Keterampilan Membaca Peserta Didik - Nurul Karimah; Afakhrul Masub Bakhtiar; Iqnatia Alfiansyah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study was made aims to: (1) Describe the development of smart reading board learning media for students reading skills (2) Describe the validation of smart reading board learning media for students reading skills (3) Describing the effectiveness of smart reading board media as learning media for student reading skills.The study uses the ADDIE development model with 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. This research was conducted at UPT SD Negeri 260 Gresik in even semester 2. The subject in this study was 1 class 15 students. This study uses data collection techniques in the form of a media questionnaire, student response validation questionnaire, reading ability and interview test sheet.The results of the research conducted are (1) Smart reading board learning media for students’ reading skills using the ADDIE development model, (2) Valuation and smart reading board learning media get a percentage of 90% by the validator of media experts, get a score of 100% by the validator of the material expert, and get percentage of 80,56 from response of students. Both of them get very good criteria, meaning extraordionary achievements, there are no shortscomings and are very satisfying. For the results of the reading skill test sheet get a percentage of 93,33% where 14 of 15 students are declared complete with KKM>75%.